THE UTILIZATION OF THE CAT'S WHICH PLANTS AS A TRADITIONAL MEDICINE FOR URINARY TRACT DISEASES IN GUGUAK NUNANG VILLAGE KEC. GUGUAK REGENCY 50 KOTA - Annisa Kharimah; Skunda Diliarosta (Department of Science Education, 2022)
This paper aims to describe the benefits of traditional medicinal plants and how to use them by the community and their suitability as a medium of information for the community in Desa Guguak Nunang, Kecamatan Guguak, Kabupaten 50 Kota. This research is a descriptive research with interview method with data collection using roaming and observation techniques. The results of interviews and research obtained 3 types of medicinal plants for this cat's whiskers, namely white-flowered cat whiskers, blue-flowered cat whiskers, and white-flowered cat whiskers, but the leaves and stems are reddish brown. in color. And what grows a lot in this area is a white flowered cat whiskers. The part that is used is the leaves. Usually made into tea with seram leaves first then doused with warm water.